2017
DOI: 10.1186/s12881-017-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Two novel compound heterozygous BMP1 mutations in a patient with osteogenesis imperfecta: a case report

Abstract: BackgroundOsteogenesis imperfecta (OI) is a collagen-related bone dysplasia leading to a susceptibility to fractures. OI can be caused by mutations in several genes including BMP1. It encodes two isoforms, bone morphogenetic protein 1 (BMP1) and mammalian tolloid (mTLD); both have proteolytic activity to remove the C-propeptide from procollagen.Case presentationWe report a Thai OI patient who had his first fracture at the age of three months. Using next generation sequencing, we successfully identified two nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…Asharani and colleagues found detectable plasma P1CP at levels just below the normal range in two patients with mutations that affected the signal peptide of BMP1, which confirmed that cleavage of the C‐propeptide occurred, suggesting that alternate enzymes facilitated the event. To date, 18 people with OI due to BMP1 mutations have been described . They share some phenotypic features with those with substrate alterations—white sclerae and absence of dentinogenesis imperfecta—but their fracture phenotype is more severe: 28% had fractures in utero or at birth and 85% had fractured by the age of 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asharani and colleagues found detectable plasma P1CP at levels just below the normal range in two patients with mutations that affected the signal peptide of BMP1, which confirmed that cleavage of the C‐propeptide occurred, suggesting that alternate enzymes facilitated the event. To date, 18 people with OI due to BMP1 mutations have been described . They share some phenotypic features with those with substrate alterations—white sclerae and absence of dentinogenesis imperfecta—but their fracture phenotype is more severe: 28% had fractures in utero or at birth and 85% had fractured by the age of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 18 people with OI due to BMP1 mutations have been described. (30)(31)(32)(33)(34)(35)(36)(37) They share some phenotypic features with those with substrate alterationswhite sclerae and absence of dentinogenesis imperfecta-but their fracture phenotype is more severe: 28% had fractures in utero or at birth and 85% had fractured by the age of 2 years. High bone density has been found in some, but not all, patients with BMP1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype-phenotype correlation gives clues to general developmental biology and is important for genetic counseling 25, 26. It has been shown that the mutations affecting glycine residues in the Gly-X-Y triplet domain of the type I collagen triple helix, compared with haploinsufficiency mutations, are responsible for more severe phenotypes including extensive skeletal abnormalities, low bone mineral density, short stature, dentinogenesis imperfecta, and scoliosis 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 18 people with OI due to BMP1 mutations have been described. (30)(31)(32)(33)(34)(35)(36)(37) They share some phenotypic features with those with substrate alterations-white sclerae and absence of dentinogenesis imperfecta-but their fracture phenotype is more severe: 28% had fractures in utero or at birth and 85% had fractured by the age of 2 years. High bone density has been found in some, but not all, patients with BMP1 mutations.…”
Section: Discussionmentioning
confidence: 99%